Bernard Labadie conducts Haydn and Handel - With Lydia Teuscher, Allyson McHardy, James Gilchrist, and Tyler Duncan Les Violons du Roy and La Chapelle de Québec - Handel, George Frideric 1685-1759; Haydn, Joseph 1732-1809 (ProdCan Inc. with the participation of medici.tv, 2018)
The 62 musicians and choristers of Les Violons du Roy and La Chapelle de Québec perform two choral masterpieces by two of the 18th century's greatest composers, Handel and Haydn. Under the baton of Bernard Labadie, they present Haydn's Mass in B-flat Major and Handel's Ode for St. Cecilia's Day--two late works of the composers. They are joined by four outstanding soloists: soprano Lydia Teuscher, mezzo-soprano Allyson McHardy, tenor James Gilchrist, and baritone Tyler Duncan. Photo: Les Violons du Roy and La Chapelle de Québec © Marc Giguère This project was made possible by the financial support of the government of Quebec and Quebec City in accordance with the Entente de développement culturel (Cultural Development Agreement).
Keywords: Choruses, Secular (Mixed voices) with orchestra; Masses; concert; Internet videos; Filmed performances; Art music